2016
DOI: 10.1097/inf.0000000000001143
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Decrease in Gastroenteritis-related Deaths and Hospitalizations in Children Less Than 5 Years of Age After the Introduction of Rotavirus Vaccination

Abstract: GE-related DCRDs, HDs and hospitalizations were significantly reduced in <1 and in 1- to <5-year-old Brazilian children after Rotarix introduction, which provides additional evidence of the direct and indirect population-level effect of RV vaccination on GE-related mortality and morbidity in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…14 In keeping with the findings from this study, other studies from Ghana have also reported genotypes P [4], P [6], and P [8], with the P [6] genotype being the most prevalent. 7,15 Strains with the VP7/VP4 genotypes: G3P [6], G12P [8], G1P [8], and G9P [4] were the most prevalent and accounted for 68% of the characterized strains, which differs somewhat from genotype prevalence reported previously-G2P [6], G3P [4] and G9P [8] as the most prevalent strains in northern Ghana, 16 and G1P [8], G3P [6], and G2P [6] as the most prevalent strains in southern Ghana. 14 The global emergence of the G12 strains in the postvaccine introduction era 17 probably explains the high incidence of the G12P [8] strain found in this study.…”
Section: Rva Prevaccine Introduction Era Surveillance Studies Havesupporting
confidence: 85%
See 4 more Smart Citations
“…14 In keeping with the findings from this study, other studies from Ghana have also reported genotypes P [4], P [6], and P [8], with the P [6] genotype being the most prevalent. 7,15 Strains with the VP7/VP4 genotypes: G3P [6], G12P [8], G1P [8], and G9P [4] were the most prevalent and accounted for 68% of the characterized strains, which differs somewhat from genotype prevalence reported previously-G2P [6], G3P [4] and G9P [8] as the most prevalent strains in northern Ghana, 16 and G1P [8], G3P [6], and G2P [6] as the most prevalent strains in southern Ghana. 14 The global emergence of the G12 strains in the postvaccine introduction era 17 probably explains the high incidence of the G12P [8] strain found in this study.…”
Section: Rva Prevaccine Introduction Era Surveillance Studies Havesupporting
confidence: 85%
“…genome is made up of 11-gene segments encased within three icosahedral protein shells. 4 Global epidemiologic surveys have identified G1P [8], G2P [4], G3P [8], G4P [8], G9P [8], and G12[P8] as the most common circulating strains associated with diarrhea in humans, 3,4 but the prevalence of the common strains has been shown to fluctuate in different geographical regions. 5 However, recent studies in developing countries have shown a greater diversity of RVA genotypes with several novel combinations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations